The Drosophila fragile X gene negatively regulates neuronal elaboration and synaptic differentiation. - Pan, L.; Zhang, Y.Q.; Woodruff, E.; Broadie, K. (Current Biology, 2004)
Fragile X Syndrome (FraX) is the most common form of inherited mental retardation. The disease is caused by the silencing of the fragile X mental retardation 1 (fmr1) gene, which encodes the RNA binding translational regulator FMRP . In FraX patients and fmr1 knockout mice, loss of FMRP causes denser and morphologically altered postsynaptic dendritic spines . Previously, we established a Drosophila FraX model and showed that dFMRP acts as a negative translational regulator of Futsch/MAP1B and negatively regulates synaptic branching and structural elaboration in the peripheral neuromuscular junction (NMJ) . Here, we investigate the role of dFMRP in the central brain, focusing on the mushroom body (MB), the learning and memory center . In MB neurons, dFMRP bidirectionally regulates multiple levels of structural architecture, including process formation from the soma, dendritic elaboration, axonal branching, and synaptogenesis. Drosophila fmr1 (dfmr) null mutant neurons display more complex architecture, including overgrowth, overbranching, and abnormal synapse formation. In contrast, dFMRP overexpression simplifies neuronal structure, causing undergrowth, underbranching, and loss of synapse differentiation. Studies of ultrastructural dfmr mutant neurons reveal enlarged and irregular synaptic boutons with dense accumulation of synaptic vesicles. Taken together, these data show that dFMRP is a potent negative regulator of neuronal architecture and synaptic differentiation in both peripheral and central nervous systems.